Clinical/paraclinical findings in dogs with Leishmania infantum (Ross, 1903) in transmission areas, Uruguay - Hernández-Russo, Zully María (2025)
Canine visceral leishmaniasis (CVL), caused by Leishmania infantum (Ross, 1903), is an emerging disease in Uruguay, posing significant public and animal health challenges. This study aimed to evaluate the relationship between clinical signs and hematological, hepatic, and renal alterations in dogs seropositive for L. infantum in Uruguay. Canids were classified according to the absence/presence of clinical signs as asymptomatic (no apparent signs of disease), oligosymptomatic (less than three clinical signs compatible with CVL), polysymptomatic (three to six clinical signs), and hypersymptomatic (with more than six clinical signs). Laboratory analysis revealed significant alterations in hematological, hepatic, and renal parameters as the number of clinical signs increased. Polysymptomatic and hypersymptomatic dogs exhibited significant decreases in erythrocytes, hemoglobin, hematocrit, mean corpuscular hemoglobin (MCH), and mean corpuscular hemoglobin concentration (MCHC), alongside increased segmented neutrophils and decreased lymphocytes. Hepatic function tests showed reductions in total and direct bilirubin, albumin, and the albumin/globulin ratio, while renal parameters suchas urea and creatinine increased significantly with clinical severity. The multidimensional analysis highlighted distinct clusters of clinical signs and laboratory parameters that reflect the systemic effects of the disease. These findings highlight the progressive nature of CVL, characterized by worsening of erythropoiesis, hepatic dysfunction, and renal impairment. The study emphasizes the importance of early diagnosis and monitoring of clinical and laboratory parameters to manage this emerging disease effectively. The emergence of CVL in Uruguay calls for increased surveillance and control measures to mitigate its impact on both canine and human populations.